Rasgos de personalidad que motivan al emprendimiento en mujeres entre los 20 y 40 años de edad del corregimiento de La Paila, Valle del Cauca (2022)
The aim of this research is to analyze the personality traits that encourage entrepreneurship in women aged between 20 and 40 in the town of La Paila, Valle de Cauca. To gather the required information, a non-experimental quantitative methodology was used, including a descriptive, cross-sectional study, using 16 PF (16 Personality Factors) and a survey to help identify the human factors of the businesswomen/entrepreneurs and their impact in the results of their work. These instruments were applied to 23 women between 20 and 40 years old. The results of the study showed that most of the surveyed women are independent, objective, stable and flexible.